2022
DOI: 10.1039/d2nj00760f
|View full text |Cite
|
Sign up to set email alerts
|

Controlled compositions of tellurium/vanadium co-doped into hydroxyapatite/ε-polycaprolactone for wound healing applications

Abstract: Hydroxyapatite (HAP) was co-doped with tellurium and vanadium ions via the co-precipitation method. Pure HAP nanoparticles were embedded through polymeric materials, such as polycaprolactone (PCL) to improve and upgrade its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Due to the large pore size of the aerogels, more significant infiltration of BMSCs and promotion of their proliferation and migration were expected. 50,51 From the results, we found that the pore sizes of A-PCL, A-PHA5, A-PHA7.5, and A-PHA10 aerogels gradually decreased with the increase of n-HA concentration. This is mainly because the higher the n-HA concentration, the more complex the dispersion of n-HA in PCL solution.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Due to the large pore size of the aerogels, more significant infiltration of BMSCs and promotion of their proliferation and migration were expected. 50,51 From the results, we found that the pore sizes of A-PCL, A-PHA5, A-PHA7.5, and A-PHA10 aerogels gradually decreased with the increase of n-HA concentration. This is mainly because the higher the n-HA concentration, the more complex the dispersion of n-HA in PCL solution.…”
Section: Resultsmentioning
confidence: 91%
“…However, the extensive addition of n-HA may lead to a higher risk of aggregation in fibers and poorer mechanical effects. 49,50 The tensile strength of different aligned nanofiber membranes was measured, respectively (Fig. S4 †), and the tensile stress-strain curves of aligned nanofiber membranes with varying concentrations of n-HA are shown in Fig.…”
Section: Characterization Of the Composite Scaffoldsmentioning
confidence: 99%
“…The rough topography of all films may be advantageous for cell adhesion and crucial for dermal and epidermal tissue regeneration 52 . The authors' previous studies 53 57 revealed that the rough surfaces of the biomaterials are suitable for accelerating cell adhesion, proliferation, and skin regeneration. The rough surfaces display a high surface area, improving cell attachment, which is beneficial for their antimicrobial wound dressings and as tissue regeneration scaffolds to induce the adhesion of dermis fibroblasts.…”
Section: Resultsmentioning
confidence: 99%